Ground gas handbook - Wilson, Steve (Civil engineer); Card, Geoff; Haines, Sarah, 1966- (Whittles Publishing ; Distributed in North America by CRC Press, 2009)
With the increasing development of brownfield and landfill sites, ground gas is a common problem encountered by engineers and scientists and this book not only raises awareness of the phenomenon but also provides practical solutions to the difficulties experienced. This vital new handbook provides practical guidance to engineers, regulators and designers about assessing ground gas risk and the design of appropriate protection measures. It includes a great deal of information that has never before been available in one volume and draws on the collective experience of the authors. The book discusses the assessment of ground gas for Part II A sites and also includes information on the assessment of vapours. It provides information on gas generation and the analysis of gas flows in the ground, including the design of gas protection systems. It explains how to use the most recent assessment methods published by CIRICA, NHBC and BSI and highlights the differences between the various methods. It includes advice and recommendations about the validation and testing of protection systems as they are installed. Worked examples help explain the concepts and calculations.
Keywords: Landfill gases.; Waste gases -- Management.; Land use -- Planning.; Environmental engineering.; Land use, Urban.; Brownfields.; Sanitary landfills.; elektronické knihy; electronic books